INTEGRATION OF INFORMATION TECHNOLOGIES INTO MODERN EDUCATION - Alieksieieva , Hanna; Horbatiuk, Larysa; Kisenko , Natalia (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
This article examines the integration of information technologies into modern education and their impact on the educational system and management. It analyzes the influence of modern technologies on intensifying the educational process, individualizing learning, and improving management processes in educational institutions. The main benefits of automating documentation and methodological support, which contribute to optimizing the activities in educational institutions and improving the infrastructure of education, are described. Suggestions for further use of information technologies to develop the intellectual potential of society are made.